Evaluation of Heart Fatty Acid Binding Protein (H-FABP) As A Diagnostic Marker in Acute Coronary Syndrome - Dr. saba; Dr. Usman Ali; Dr Adnan Mustafa Zubairi; Dr. Erum Salim; Dr. Nida Haider; Dr Aisha Habib (ziauddin University, 2024)
Background: Heart Type Fatty Acid Binding Protein (H-FABP) is a biomarker suggested for early detection of Acute Coronary Syndrome (ACS). Early diagnosis and management are critical as it could prevent and reduce morbidity and mortality. The study aimed to determine the diagnostic accuracy of H-FABP as a biomarker of ACS compared to gold standard high-sensitivity Troponin I (hs-TnI) and/or ECG findings suggesting ischemia. Methods: The study was conducted from May 2020 to November 2020 at Dr. Ziauddin University Hospital in Karachi. Blood samples of 154 patients were collected, who presented to an emergency department or admitted to the Cardiac Care Unit more than 18 years of age with symptoms suggesting angina as pain in the chest, left arm/lower jaw, increased heart rate and shortness of breath. Patient data regarding age, gender, duration of chest pain onset, kidney disease, diabetes mellitus, hypertension and smoking were collected. Serum H-FABP was analyzed on a Quantitative Fluorescence immunoassay Analyzer. Diagnostic accuracy statistics for H-FABP were calculated with the help of contingency tables taking hs-TnI and/or ECG findings as a gold standard. Results: Overall H-FABP showed sensitivity (91.0%), specificity (76.7%), PPV (90.9%), NPV (76.7%) and diagnostic accuracy was 87.58%. H-FABP demonstrated an Area Under Curve (0.911, 95% C.I:0.850-0.972, p<0.001), higher than that of hs-TnI (0.908, 95% C.I:0.844-0.971, p<0.001) in patients having chest pain for 3 hours or less, at the cost of specificity. Conclusion: H-FABP is a more sensitive biomarker than hs-TnI in the early diagnosis of ACS (p<0.001). However, being less specific, it can be used as an adjuvant cardiac biomarker for early diagnosis of ACS. Keywords: Diagnostic Accuracy, Acute Coronary Syndrome; Heart-Type Fatty Acid Binding Protein; Cardiac Biomarkers.